Observed Mass Balance of Mountain Glaciers and Greenland Ice Sheet in the 20th Century and the Present Trends - Ohmura, Atsumu (2018)
Glacier mass balance and secular changes in mountain glaciers and ice caps are evaluated from the annual net balance of 137 glaciers from 17 glacierized regions of the world. Further, the winter and summer balances for 35 glaciers in 11 glacierized regions are analyzed. The global means are calculated by weighting glacier and regional surface areas. The area-weighted global mean net balance for the period 1960-2000 is −270±34mma−1w.e. (water equivalent, in mm per year) or (−149±19km3a−1w.e.), with a winter balance of 890±24mma−1w.e. (490±13km3a−1w.e.) and a summer balance of −1,175±24mma−1w.e. (−647±13km3a−1w.e.). The linear-fitted global net balance is accelerating at a rate of −9±2.1 mm a−2. The main driving force behind this change is the summer balance with an acceleration of −10±2.0mm a−2. The decadal balance, however, shows significant fluctuations: summer melt reached its peak around 1945, followed by a decrease. The negative trend in the annual net balance is interrupted by a period of stagnation from 1960s to 1980s. Some regions experienced a period of positive net balance during this time, for example, Europe. The balance has become strongly negative since the early 1990s. These decadal fluctuations correspond to periods of global dimming (for smaller melt) and global brightening (for larger melt). The total radiation at the surface changed as a result of an imbalance between steadily increasing greenhouse gases and fluctuating aerosol emissions. The mass balance of the Greenland ice sheet and the surrounding small glaciers, averaged for the period of 1950-2000, is negative at −74±10 mma−1w.e. (−128±18km3a−1w.e.) with an accumulation of 297±33mma−1w.e. (519±58km3a−1w.e.), melt ablation −169±18mma−1w.e. (−296±31km3a−1w.e.), calving ablation −181±19mma−1w.e. (−316±33km3a−1w.e.) and the bottom melt-21±2mma−1w.e. (−35±4km3a−1w.e.). Almost half (−60±3km3a−1) of the net mass loss comes from mountain glaciers and ice caps around the ice sheet. At present, it is difficult to detect any statistically ...